Hubungan Tingkat Kebugaran Fisik terhadap Kejadian Sesak Napas dan Risiko Hipotermia pada Pendaki Pemula Gunung Sibayak - Rizki Kurniati; Joka Novetra; Danang Pujo Broto; Apriyanti Rahmalia; Bangkit Seandi Taroreh; Rasyono Rasyono (Indonesian Journal of Sport and Tourism, 2025)
This study aims to analyze the relationship between physical fitness levels and the occurrence of shortness of breath and hypothermia risk among novice climbers on mount sibayak, karo regency, north sumatra. The research employed a quantitative approach with a descriptive correlational design and a cross-sectional method. The sample consisted of 60 university students aged 20–24 years who participated in community service (kkn) activities and conducted mountain climbing. Physical fitness was measured using the harvard step test, shortness of breath was assessed using the borg dyspnea scale, and hypothermia risk was evaluated through body temperature measurements and clinical symptom observations. The results showed a strong negative correlation between physical fitness level and shortness of breath (r = -0.682; p = 0.001), and a moderate negative correlation between physical fitness and hypothermia risk (r = -0.543; p = 0.004). In addition, a moderate positive correlation was found between shortness of breath and hypothermia risk (r = 0.516; p = 0.007). These findings indicate that higher levels of physical fitness are associated with lower risks of respiratory disturbance and body temperature decline during mountain climbing. This study recommends the implementation of pre-climb physical fitness training and physiology-based safety education programs to enhance preparedness and safety among novice climbers in extreme environments.